(untitled) (Bodhi Path, 2020)
Asceticism has always been part of the spiritual practices even before the Buddha, there used to be a common belief that if one indulges in one’s senses or suppresses them, then one would ultimately reach the purification of mind .So there were two extremes which were sought after to find satisfaction and peace of mind, one of the extreme was the sensual indulgence and another was self mortification practice.So after understanding the limitations of these two extremes, Buddha decided to practice the middle way which avoids both extremes and thus after walking the middle way he reached to the direct understanding into the real nature of phenomenal world in terms of three characteristics of transitoriness ,suffering and selflessness. Asceticism in Pre Buddhist Period i.e. the Ascetic practices of Three traditions namely- Vedic Religion, Jains (Nigantha Ascetics) and Ajivikas(naked ascetic wanderers) had their influence on Buddha’s Quest. Various types of a Ascetic practices of Pre Buddhist era related to Basic requisites of Ascetics (food ,clothing and shelter ) had a deep influence on Buddha’s spiritual training .Buddha after realizing that the extreme self mortification practices are not conducive for achieving the higher goal, also guided other Ascetics to avoid self mortification practices as clearly mentioned in the second Sutta of Patthika Vagga of Digha Nikaya which is Udumbarika sutta given to Ascetic Nigrodha who was a wandering Ascetic. Thus this Research paper will deal with the different phases of Buddha’s Quest as depicted in Majjhima Nikaya.